Sistem Informasi Geografis Penentuan Lahan Potensial Menggunakan Image Processing - Darwinta, Hendra; Wijaya, Harianto T.; Taufik, Vicky M. (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2012)
The expansion of marketing areas is the mission that needs to be done by all companies, including by PT. DAPI (DuPont Products Agriculturan Indonesia). One cause of the difficulty of PT DAPI to expand the marketing area is the lack of information on potential land in Indonesia. Not to mention the vast area of Indonesia with a few islands and some areas are still a wilderness that is difficult to reach. DuPont currently do not have a system that can analyze potentially useful area to be a reference to conduct target marketing area expansion. Potential area is the area of the earth's surface that has the potential to grow something crops. The condition can be a potential area of forest and fallow areas by plants. Image Processing is the process of processing data in the form of images, where the process will process map which is also an image. Image processing method used to determine potential areas for planting a crop with the selection of a particular color on the surface of the earth. The results of the surface of the earth will diggabungan with the results of analysis of the potential growth of plants by altitude. According to climate Junghuhn associated with plants that grow and produce in accordance with the temperature optimum habitat. Conclusions drawn from the manufacture of this system is Geographic Information Systems Land Potential Determination Using Image Processing has been successfully designed, is built and implemented so as to produce the analysis of potential areas located in Indonesia by applying image processing to analyze the height map and map the Earth's surface. Results of analysis of Geographic Information Systems can also be used by other GIS applications for Geographic Information System is dead save into a format commonly used by GIS applications. Results of analysis of Geographic Information Systems can be used as a reference PT DAPI to help determine the areas of marketing expansion.